ICT for growth and equality : renewing strategies for the information society : summary (UN ECLAC SantiagoCL, 2010)
States that there is no significant narrowing of the gap with countries of the OECD, as to the degree of readiness for the information society. Notes that the impact of ICT in the countries of the region has been modest in comparison with international best practices, and the rise in spending on ICT as a proportion of GDP has not been matiched by increases in productivity even though a variety of programmes and strategies for the information society have been implemented since the late 1990s. Calls for a second generation of digital development and inclusion strategies based on greater coordination between institutions.
Keywords: INFORMATION SOCIETY